Patient posture for blood collection by venipuncture: recall for standardization after 28 years - Lima-Oliveira, Gabriel (Rev Bras Hematol Hemoter, 2017)
BACKGROUND: Although data about the effect of posture on routine hematological testing were published 28 years ago, this pre-analytical issue has not been standardized so far. This study was planned to evaluate whether postural changes influence the results of hematology testing. METHODS: A complete blood count was performed in 19 healthy volunteers after 25 min in the supine position, 20 min in a sitting position and 20 min stationary standing in an upright position. RESULTS: The change from supine to sitting position caused clinically significant increases in the hemoglobin, hematocrit and red blood cell count. Furthermore, the change from supine to standing caused clinically significant increases in the hemoglobin, hematocrit, red blood cell, leukocyte, neutrophil, lymphocyte, basophil and platelet counts, and mean platelet volume, and that from sitting to standing caused clinically significant increases in hemoglobin, hematocrit, and red blood cell, leukocyte, neutrophil and lymphocyte counts. CONCLUSION: The results of this investigation provide further support to the notion that effort should be made to achieve widespread standardization in the practice of phlebotomy, including patient posture.